1982
DOI: 10.1037/0022-0663.74.1.111
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between student personality characteristics, teacher ratings, and student achievement.

Abstract: Three studies examined the relationship between student personality characteristics, teacher ratings, and student achievement. In Study 1, students (N = 388) (a) rated themselves on the Adjective Check List (ACL), (b) viewed one of four color videotapes that varied in instructor expressiveness (low, high) and lecture content (low, high), (c) completed an evaluation of the videotaped instructor and a test on the lecture, and (d) completed the ACL for the instructor. Study 2 was similar except students (N -87) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 38 publications
3
26
0
1
Order By: Relevance
“…In a recent study, Abrami, Perry, and Leventhal (1982) explored the relationship between student personality characteristics and course ratings. They found that student personality characteristics did not account for a meaningful amount of variance in ratings.…”
mentioning
confidence: 99%
“…In a recent study, Abrami, Perry, and Leventhal (1982) explored the relationship between student personality characteristics and course ratings. They found that student personality characteristics did not account for a meaningful amount of variance in ratings.…”
mentioning
confidence: 99%
“…While students' cognitive ratings of teaching may be valid indicators of teaching effectiveness (Page, 1974;Cohen, 1981;Abrami, 1982), our findings suggest that male Undergraduates with less vocational commitments may feel relatively less satisfied with their courses. There is evidence that such dissatisfied male students would be over-represented on Arts courses.…”
Section: Discussionmentioning
confidence: 52%
“…Teaching is a multidimensional activity and measuring the effects of instruction is difficult because no single criterion of effectiveness is widely accepted (Abrami, 1993;Abrami & Mizener, 1983;Abrami et al, 1996;Abrami et al, 1982;Marsh, 1983Marsh, , 1984Marsh, , 1987Marsh, , 1994Marsh, , 1995. And, while student learning and motivation for continued studies are valuable indicators of instructional effectiveness (cf.…”
Section: Alternate Approachesmentioning
confidence: 98%